PERAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) PROVINSI BENGKULU DALAM PELATIHAN PETUGAS LAPANGAN KELUARGA BERENCANA (PLKB) - Eli Ermawati; Antonio Imanda; Asnawati Asnawati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2018)
This research was conducted at BKKBN Branch office bengkulu Province, training and developing (Latbang). This research purpose is to find out the role of BKKBN Bengkulu province in Training of Family Planning field officer. This research uses descriptive qualitative method. Data is collected thru observation, interview and documentation. Faried Ali (2011) theory is used in this research. The result of this research shows that the roles of BKKBN in PLKB training are: (1) Stabilizator, PLKB can increase the knowledge and ability in PLKB Training, it can be seen from pre-test and post-test. But not in all PLKB trainers can increase their skills because some of them weren’t listening or taking a note, some of them playing with their smartphone and talking; (2) Dinamisator, the process of PLKB training started by holding a preparation meeting. In that meeting, materials are discussed, training time, administration preparation like correspondence and financial, also facility in training; (3) Inovator, BKKBN found new things in PLKB Training because there was an evaluation after training, observation, suggestions, all trainees can give suggestion about the training. BKKBN also give material according to PLKB need and has provide the material professionally because they split time into discussion, working group, field practive, refreshing (outbound) and follow-up.